Maker Conversation: Successes and Challenges in a University SALC - Jamison Taube-Shibata; Andria Lorentzen (Studies in Self-Access Learning Journal)
This paper discusses the implementation of Maker Conversation, a self-access learning space in a university’s Self-Access Learning Center (SALC) during the 2022 academic year. Maker Conversation is aimed at promoting English language use among students through science, technology, engineering, art, and mathematics (STEAM) activities and is based on the Maker Movement. After introducing the maker concept and explaining the rationale for adapting maker principles to fit into the university’s SALC, two facilitators who participated in Maker Conversation reflect on their experiences during the academic year. This paper highlights the successes of Maker Conversation for both students and facilitators, as well as the challenges that facilitators faced. Future plans that address these challenges are discussed. The facilitators felt that Maker Conversation provides valuable learning opportunities and plan to further develop and enhance the program for students and facilitators. This paper may benefit educators at other institutions who are interested in implementing their own version of Maker Conversation in their SALC.